Control of exposure to hexavalent chromium concentration in shielded metal arc welding fumes by nano-coating of electrodes. (3rd April 2017) - Sivapirakasam, S. P.; Mohan, Sreejith; Santhosh Kumar, M. C.; Thomas Paul, Ashley; Surianarayanan, M.
Abstract: Background : Cr(VI) is a suspected human carcinogen formed as a by-product of stainless steel welding. Nano-alumina and nano-titania coating of electrodes reduced the welding fume levels. Objective : To investigate the effect of nano-coating of welding electrodes on Cr(VI) formation rate (Cr(VI) FR) from a shielded metal arc welding process. Methods : The core welding wires were coated with nano-alumina and nano-titania using the sol-gel dip coating technique. Bead-on plate welds were deposited on SS 316 LN plates kept inside a fume test chamber. Cr(VI) analysis was done using an atomic absorption spectrometer (AAS). Results : A reduction of 40% and 76%, respectively, in the Cr(VI) FR was observed from nano-alumina and nano-titania coated electrodes. Increase in the fume level decreased the Cr(VI) FR. Discussion : Increase in fume levels blocked the UV radiation responsible for the formation of ozone thereby preventing the formation of Cr(VI).